Development of a human-guided micro-manipulation system - Kong, Kah Yooi (2018)
In the field of material science, bioengineering and physics research, micro-manipulation has played a significant role in the development of technology. Micro-manipulation is the control of microscopic objects using instruments such as optical tweezers. In recent time, much attention has been given to optical tweezers because of their capability to manipulate microscopic objects without any physical contact with them. The objective of this project was to develop a system whereby the user can control the motorized XY stage of the Eclipse Ti-U remotely. With a microscopic object trapped at a position, it could be moved around in between the microscopic glass slides by moving the stage. The Xbox 360 controller was used to control the stage from a remote computer. A video of the micro-environment could be viewed while moving the stage. The objective of the project was achieved by developing two LabVIEW programs which uses Transmission Control Protocol to communicate with each other. The remote computer program could transmit the signal to control the stage at the laboratory computer program. It could also receive the position of the stage from the laboratory computer and display the route of the stage and the microscopic object. Lastly, the position versus time graph was plotted to determine the speed of the stage.